Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Keterampilan Proses Sains dan Hasil Belajar IPA Siswa - Elyas Djufri; Trio Ardhian (Jurnal Ilmiah Profesi Guru (JIPG), 2021)
This research aims to investigate the effect of guided inquiry learning model upon scienific attitude and science learning achievement which uses the posttest-only control group design. This  research is conducted at fourth  grade students of SD Negeri Kecamatan Galang. The reseach  population  are 125 students samples are 64 students. Data of scientific attitude was collected by using observationmethod, and  the  data  of  science  learning achievement was collected by using test method. The data was analyzed using SPSS 20.00 for windows bases MANOVA. The rsults show that: (1) there are significant differences of science process skill and science learning achievement between  student  studying  by  using guided inquiry learning  model  and  conventional learning model (p<0.05),  (2) There  is significant difference of science process skill between student studying by using guided inquiry learning model and conventional learning model (p<0.05), (3) There is significant difference of science learning achievement between student studying by using guided inquiry learning model and conventional learning model (p<0.05)